(untitled) (Revista Tempo e Argumento, 2016)
The Movimiento de Izquierda Revolucionaria (MIR) of Chile, was a political-military organization, ideologically attached to Marxism-Leninism, but also inheritor in the political and symbolic level of the Cuban Revolution and Guevarism. The MIR was founded in August 1965, and has extensive and relevant political career. Nevertheless, the studies on the MIR are still scarce and multiple aspects associated with their insertion in the political history of Chile in the last third of the 20th century, remain unknown. In this article we analyze the historical conditions in which the Chilean MIR was formed and its contribution to the process of political radicalization that took place in Chile between 1967 and 1973. Similarly, its ability to react to the repressive violence deployed by the dictatorship from 1973 and its role in organizing popular resistance are also studied.